Studi Orientalisme Menurut Sejarah dan Tujuan Gerakannya - Nurachman, Azhar; Mujahid, Kasori (AHKAM, 2023)
This article will elaborate in detail on Orientalism from a historical perspective. The study of Orientalism is complex, especially concerning the Orient, particularly Islam, and is driven by motives such as religious, scientific, economic, and political issues. The terms "Orientalism" and "Orientalist" emerged in Andalusia (Spain) in the 7th century Hijri or the 14th century AD. They have harmed Islam by submerging Muslims into misleading ideologies, particularly misleading the younger generation by diverting them from their religion through teachings of materialism and secularism. The stages of Orientalism development include Missionaries and anti-Islamic sentiments beginning in the 16th century AD, studies and dissemination in the 17th and 18th centuries, colonialism in the 19th century and the first quarter of the 20th century, and learning and politics in the latter half of the 19th century. The main goal of Orientalism is to uncover and reveal the symbolic meanings of deep-rooted Islamic cultural expressions, with the primary medium being the Arabic language.